Institusionalisasi pemikiran pendidikan Mohammad Natsir ke dalam lembaga Pendidikan Tinggi Islam di Indonesia - Waskito, Tejo (Ta'dibuna: Jurnal Pendidikan Islam, 2023)
This research aims to investigate the institutionalization process of Mohammad Natsir's educational thoughts in Islamic higher education institutions in Indonesia. Qualitative research method was used in this study with document analysis technique as the main data source. The data obtained were then analyzed using content analysis. The results of the study show that Mohammad Natsir's educational thoughts were institutionalized through various efforts, one of which was the establishment of the Islamic College as a higher education institution that adopted Mohammad Natsir's vision and ideas, especially in the development of curriculum and the provision of education that integrates Islamic and Western education models. This institutionalization was also carried out through the development of a curriculum that emphasizes the provision of academic education in a balanced practice. In conclusion, Mohammad Natsir's educational thoughts were successfully institutionalized through the establishment of the Islamic College which later evolved into the Indonesian Islamic University, and provided important contributions to the development of modern and quality Islamic education in Indonesia. Abstrak Penelitian ini bertujuan untuk menginvestigasi proses institusionalisasi pemikiran pendidikan Mohammad Natsir dalam lembaga pendidikan tinggi Islam di Indonesia. Metode penelitian kualitatif digunakan dalam penelitian ini dengan teknik analisis dokumen sebagai sumber data utama. Data yang diperoleh kemudian dianalisis dengan menggunakan analisis konten. Hasil penelitian menunjukkan bahwa pemikiran Pendidikan Mohammad Natsir diinstitusionalisasikan melalui berbagai upaya, salah satunya adalah dengan pendirian Sekolah Tinggi Islam sebagai lembaga pendidikan tinggi yang mengadopsi visi dan gagasan Mohammad Natsir, utamanya dalam pengembangan kurikulum dan penyelenggaraan pendidikan yang mengintegrasikan model pendidikan Islam dan Pendidikan Barat. Institusionalisasi tersebut juga dilakukan melalui pengembangan kurikulum yang menekankan pada penyelenggaraan pendidikan akademik dalam praktik yang seimbang. Kesimpulannya, pemikiran pendidikan Mohammad Natsir berhasil diinstitusionalisasikan melalui pendirian Sekolah Tinggi Islam yang kemudian berevolusi menjadi Universitas Islam Indonesia, dan memberikan kontribusi penting dalam pengembangan pendidikan Islam modern dan berkualitas di Indonesia.